Association of subclinical hypothyroidism with atherosclerosis in central India - Upadhyay, Vibhor; Deopujari, K.; Dubey, T.N.; Sharma, A; Tripathi, Pooja (International Journal of Medical Research and Review, 2017)
Introduction: Overt hypothyroidism is widely recognized as a risk factor for atherosclerosis and cardiovascular disease, but recently sub clinical hypothyroidism has also shownas an independent risk for it. Subclinical hypothyroidism also has close association with dyslipidemia and lowgrade inflammation leading to atherosclerosis which can be assessed by carotid intimal medial thickness. Objective: The objective of the study was to explore the correlation of subclinical hypothyroidism with atherosclerosis in the form of dyslipidemia, C Reactive Protein and Carotid Intimal Medial Thickness in patients of central India. Methods: This study was conducted at department of medicine in GMC, Bhopal. It was a case control study among which 100 patientswith raised TSH and normal T3/T4 values were included as cases in the study and 50 controls with normal TSH/T3/T4 were taken. Three groups were made according to TSH values as euthyroids (<5.5), Subclinical Hypothyroids group 1(5.5-10) & group2(>10) and their fasting lipid profile, C Reactive Protein levels and Carotid Intimal Medial Thicknesswere measured. Results: We compared the Subclinical Hypothyroids with euthyroids subjects in which lipid profile was highly significant (<0.01)and showed positive correlation in both groups of Subclinical Hypothyroids except for high density lipoprotein.In cases where TSH(>5.5) the CRP was found to be significantly associated showing presence of low grade in flammation in these patients. The study also showed that mean Carotid Intimal Medial Thickness was higher in Subclinical group as compared to euthyroids but only when TSH(>10). Conclusion: This study concludes that subclinical hypothyroidism is characterized by dyslipidemiawith increased Carotid medial intimal thickness value and positive CReactive Protein suggesting the future development of cardiovascular disease in these patients.